(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper is the result of a thirty hour seminar on Performance Studies, taught by Dr. Carmela Cutugno at the University of Bologna, as part of a Master course in Theories and Cultures of Representation held by Professor Marco De Marinis. The idea for the chosen topic, as well as part of the readings were suggested during the seminar by Dr. Cutugno, who assisted us for the entire process of thinking and writing about this issues. The seminar was conceived and realized as a performance studies analysis workshop and the final paper was presented, performed and danced as the result of the course. This essay is a synopsis of that work, focused on Voguing, firstly as artistic and cultural performance, and then upon the differences between the U.S.A. context and the Italian context, which were both supported by the dichotomy between artistic performance and “gender performativity”. The first part of this essay starts from this point to analyze the process of transformation, and differentiation of the voguing culture, paying particular attention to the Italian performative scene. In the second part a further analysis is carried out, taking into account all the topics connected to the ideas of identity and gender.